TRANSFORMASI HUKUM ISLAM KE DALAM BENTUK QANUN DAULI DUSTURI - Muchsin, Agus (DIKTUM: Jurnal Syariah dan Hukum, 2014)
This article out lines nasalah Transformation of Islamic lawin the form of Qabun Dauli Dusturi. From there sults of the discussion can be understood that Islamic law in some modern state can be viewed from two aspects; Islamic law applicable formal judicial and normative, which is described by the three forms of implementation of Islamic law, namely: (1) the implementation of Islamic law through state intervention, by form alizing Islamic law instate legislation. (2) The implementation of Islamic law by way of transformation of the values of Islamic law in the system of state regulation, without form alizing symbolically. (3) The implementation of Islamic law to separate the religious affairs of the state structure, so that the implementation of Islamic law is categorizedas an individual problem. Construction methodology of Islamic law in general consistof: Patterns Bayani, Ta'lili and Istilahi. Viewed from the standpoint of methodology, the phenomenon of Islamic legal thought in general shows that there are at least twoways of thinkingt hat; Islamic legal thought liberal and conservative Islamic legal thought textual.